Fuzzy GIS‐based multi‐criteria evaluation for US Agave production as a bioenergy feedstock. Issue 1 (28th February 2014) - Lewis, Sarah M.; Gross, Stephen; Visel, Axel; Kelly, Maggi; Morrow, William
Abstract In the United States, renewable energy mandates calling for increased production of cellulosic biofuels will require a diversity of bioenergy feedstocks to meet growing demands. Within the suite of potential energy crops, plants within the genus Agave promise to be a productive feedstock in hot and arid regions. The potential distributions of Agave tequilana and Agave deserti in the United States were evaluated based on plant growth parameters identified in an extensive literature review. A geospatial suitability model rooted in fuzzy logic was developed that utilized a suite of biophysical criteria to optimize ideal geographic locations for this new crop, and several suitability scenarios were tested for each species. The results of this spatially explicit suitability model suggest that there is potential for Agave to be grown as an energy feedstock in the southwestern region of the United States – particularly in Arizona, California, and Texas – and a significant portion of these areas are proximate to existing transportation infrastructure. Both Agave species showed the highest state‐level renewable energy benefit in Arizona, where agave plants have the potential to contribute 4.8–9.6% of the states' ethanol consumption, and 2.5–4.9% of its electricity consumption, for A. deserti and A. tequilana, respectively. This analysis supports the feasibility of Agave as a complementary bioenergy feedstock that can be grown in areas too harsh for conventional energy feedstocks.